The Diferences Cholesterol Level of Employees with Nutritional Status Overweight And non Overweight - Sugirah Nour Rahman; Hezron Alhim Dos Santos; Jaya, Andi Mas (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The level of colesterol plays a vital role in cardiovascular disease. Overweight and obesity can increase the occurrence of high levels of blood cholesterol (hypercholesterolemia) in otherwhise cholesterol levels are also high in people of normal weight. This study aims to compare cholesterol levels in employees with overweight and non-overweight nutritional status. This study used a cross-sectional design with a sample size of 62 respondents taken by total sampling technique. Data was collected using secondary data results from medical checkups of Tanker Division of employees. The data used a T test with a significance level of p<0.05. The percentage of overweight was 40 (64.5%), and the percentage non-overweight was 22 (35.5%). The study showed there are differences in total cholesterol levels overweight and non-overweight nutritional status with a value of p = 0.000 (p <0.05). The average cholesterol level for employees with overweight nutritional status is 195.80 mg/dl, which is higher than the average cholesterol level for non-overweight employees, which is 167.23 mg/dl. In conclusion there was significant difference between cholesterol levels of overweight and non-overweight.